Combination of Sodium Hyaluronate, Withania Somnifera Extract and Niacinamide Improves Hydration and Skin Tone – A Clinical Study - Rastogi, Rachna; Lima, Galwin D; Gholap, Anjali (Current Cosmetic Science, 2023)
BackgroundMultiple moisturizing solutions with sodium hyaluronate, Withania sominifera, and niacinamide are commercially popular. Detailed clinical studies portraying their activity are not available.ObjectiveThis study aims to study the clinical efficacy of a phyto-bioactive cream in improving skin hydration and tone with 4 weeks of continuous usage.MethodologyWe conducted a non-comparative, single-blind study on 50 Asian female volunteers with Fitzpatrick skin types III-VI for 28 days. Cosmetic acceptability and safety of the product were established via self-evaluation questionnaires. The ability of the topical formulation in maintaining skin tone, hydration, and firmness was determined by instrumental analysis and smoothness by dermatologist evaluation.ResultsA total of 46 subjects completed the study. High levels of skin hydration were noted instantaneously (+61.11%) and post continuous use of the product. Significant reduction in the appearance of age/dark spots (ITA°), Δ ITA°= 37.49% and increase in skin lightness (L) by 2.66% compared to baseline was observed in 4 weeks. More than 80% of the subjects reported an increase in skin firmness and smoothness in 4 weeks of twice-a-day product usage.ConclusionOur study establishes the safety and acceptability of the phyto-bioactive cream. The efficiency of the combination of Withania somnifera extract, sodium hyaluronate, and niacinamide in improving skin hydration and tone has been proven.
Keywords: sodium hyaluronate